Epidemiological profile of meningitis in Tocantins, from 2012 to 2021 (Research, Society and Development, 2022)
Meningitis is a disease that affects the brain meninges and can have different causes and different symptoms. This disease is considered a public health problem, due to its potential to cause epidemic outbreaks and lethality. The objective of this work is to outline a descriptive, cross-sectional and retrospective epidemiological study of meningitis cases from 2012 to 2021. The methodology applied was based on the collection of data extracted from the National Information System on Notifiable Diseases (SINAN), available at the Department of Informatics of the SUS (DATASUS). The variables included were the following: sex, age group, race, health region, etiology and evolution. From this data collection, it was observed that the year 2014 had a greater number of cases with 78 records, on the other hand, 2021 registered only 11 cases. The male gender was the most affected by meningitis with 338 cases (59.09%). The age group most affected was 20 to 39 years old with 116 notifications (20.28%), followed by children under 1 year old with 97 cases (16.96%). The brown ethnicity stands out with a total of 470 records (82.17%). In relation to health regions, Medio Norte Araguaia had the highest number of cases with 253 (44.23%). The viral etiology was the most present (35.66%). About 48 deaths have been documented. It is concluded that this work is of fundamental importance for the development of health practices to better serve the population of Tocantins.